posted by Lauren .
All the directions say for these three problems is multiply and simplify. Are my answers correct? Thank you
A) You have a plus sign in the first one so it is add, not multiply. It is wrong anyway for adding or multiplying.
B) One way to do these is to split them up using the distributive property
(x+1)(2x-1) = x(2x-1) + 1 (2x-1)
= 2 x^2 - x + 2x - 1
= 2 x^2 + 1x - 1
C) x(x^2+2x-3) -2(x^2+2x-3)
x^3 +2x^2 -3x -2x^2 -4x +6
= x^3 -7x +6
Srry the problem for a is suppose to be 2x(x^2-3x+2) this is my answer